An atom-efficient and convergent approach to the preparation of NS5A inhibitors by C–H activation. Issue 12 (3rd March 2016) - Moore, Thomas O.; Paradowski, Michael; Ward, Simon E.
Abstract : A novel approach of the convergent functionalisation of aryl dibromides to form NS5A type inhibitors using C–H activation is reported. Abstract : A novel approach of the convergent functionalisation of aryl dibromides to form NS5A type inhibitors using C–H activation is reported. The focus of investigation was to reduce the formation of homodimeric side product, as well as to investigate the scope of different aryl dibromides that were tolerated under the reaction conditions. The C–H activation methodology was found to give a viable synthetic route to NS5A inhibitors, with late stage functionalisation of the core portion of the molecule, albeit with some chemical functionalities not tolerated.